THE ROLE AND IMPORTANCE OF SIMULATIONS IN EFL CLASSES - Nazarova Dilshodakhon Ochildinovna (Journals Park Publishing, 2022)
The current article aims at providing general information about simulation, its effective use and importance in teaching English as a foreign language. The article deals with the term simulation and shows similarities and differences of simulations from other language activities, gives definitions by scientists and shows the role of simulations in foreign language learning teaching as well as improving writing and speaking skills. Suggestions, drawbacks and solutions by leading experts and how simulations are important in teaching foreign languages are discussed and proved in this article.
Keywords: simulation; game-based technologies; critical thinking skills